Soil bacteria from Muna Island, Southeast Sulawesi, Indonesia: Antibacterial and antibiofilm activities, and the presence of antibiotic-biosynthetic genes - Egiyanti Nur Widhia Hening, Jepri Agung Priyanto, Muhammad Eka Prastya, Rika Indri Astuti, La Ode Abdul Fajar Hasidu, Jamilah (Journal of Applied Pharmaceutical Science, 2024)
Unexplored soil bacteria isolated from Muna Island, Southeast Sulawesi, Indonesia, provide a new source of active molecules serving as prospective antibacterial agents. In the present research, the antibacterial and antibiofilm activities of bacterial isolates obtained from Muna Island were evaluated. Based on the preliminary screening through the antagonism assay, 5 out of the 15 isolates exhibited various spectra of antibacterial activities. At a concentration of 80 mg/ml, metabolites extracted from the two selected isolates, M7 and P1 inhibited the growth of the five multidrug-resistant strains. These extracts exhibited minimum inhibitory concentration and minimum bactericidal concentration values of 312.5 μg/ml to more than 10,000 μg/ml. An analysis of the 16S rRNA sequences revealed that the corresponding isolates were closely related to Bacillus aerius strain 24K and Priestia (Bacillus) aryabhattai strain B8W22, with >97% similarity. Some genes involved in antibiotic biosynthesis, such as mlnA, baeR, srfA, dfnD, and bacD, were also present in the bacterial genome. Liquid chromatography-tandem mass spectrometry analysis of the most potent M7 extract showed that it contained several antibacterial compounds, such as cyclo(D-Pro-L-Tyr), marinoquinoline G, and rancinamycin Ib.
Keywords: Antibacterial, antibiofilm, Bacillus, multidrug-resistant bacteria, secondary metabolite